The effect of propolis application on quality properties of vacuum-packed hot smoked rainbow trout (Oncorhynchus Mykiss, Walbaum 1792) fillets during cold storage - Gungoren, Alper; Patir, Bahri; Ozpolat, Emine (Elsevier, 2023)
This research aimed to apply propolis extract (PE) to extend the shelf life and improve the quality of hot smoked rainbow trout while avoiding apparent changes in organoleptic properties. To this end, the effect of PE at different levels (0,25%, 0,50%, 1%, and 3%) on the physico-chemical, chemical, microbiological, and sensory parameters of vacuum-packed hot smoked rainbow trout (Oncorhynchus mykiss, Walbaum 1792) fillets was investigated throughout cold storage (4 & PLUSMN; 1 degrees C). The observed shelf life of smoked trout was similar in the control and 0.25% PE groups (56 days). After two weeks (on day 70), the 0.50% and 1% PE groups were spoiled. Finally, on storage day 84, 3% of the PE group was spoiled. The dose of 0.25% PE used in this study was insufficient to show the desired effects on the final product. The application of 3% PE significantly affected the microbiological and chemical properties. However, it had a negative effect on the odor and taste of the products. The 1% PE group demonstrated the most potent sensory properties in color, odor, and overall acceptability. This study shows that 1% PE is useful in hot smoked rainbow trout fillets as a natural antimicrobial and antioxidant.
Keywords: Hot smoking; Propolis extract; Rainbow trout; Shelf life; Sensory quality